Investigating the environmental impact of reinforced-concrete and structural-steel frames on sustainability criteria in green buildings. (November 2021) - Ranjbar, Nima; Balali, Amirhossein; Valipour, Alireza; Yunusa-Kaltungo, Akilu; Edwards, Rodger; Pignatta, Gloria; Moehler, Robert; Shen, Wei
Abstract: Reducing the detrimental impact of human activities on our environment is an essential need. Buildings have a significant role in accomplishing this need, which necessitates the conduction of comprehensive research that adequately identifies the underlying factors and then seeks sustainable solutions. Green buildings have been one of the critical initiatives to lessen the negative impact of human endeavors on the environment. The structural frame is one of the most critical elements of buildings, especially owing to their impact on the environment. This study investigates how structural building frames perform according to sustainability criteria. A questionnaire was used to identify the relevant sustainability criteria, and a hybrid Delphi-SWARA model was used to determine the relative importance of eight comprehensive prioritized criteria. A building was simulated with DesignBuilder software to quantify the environmental impact of two main types of structural frames, reinforced concrete (RC) and structural steel (SS) frames, on sustainability criteria. Results illustrated that RC-framed buildings have a less detrimental impact on the environment due to less energy consumption and carbon emissions. The energy consumption in RC-framed buildings was 2.3% less in electricity consumption and 2.7 less in natural gas consumption. In addition, 88 tonnes of CO2 emission can be reduced with this type of frame in a 50-year lifecycle which is more than 5% of the total CO2 production of the building. The methodological approach used in this research introduces a novel way for decision-makers to consider the sustainability criteria in the design stage. Highlights: Buildings' sustainability criteria were identified. The identified buildings' sustainability criteria were prioritized. Impact of RC and SS frames on sustainability criteria were investigated. RC-framed buildings have a less detrimental impact on the environment.